Determination of Citric Acid Level in Starfruit (Averrhoa bilimbi L.) and Starfruit Raisins - Sri Rahayu; Nuryanti, Siti (Universitas Tadulako, 2023)
Citric acid is one of the plants in Indonesia that has many benefits in various fields, especially in the industry. This study aims to determine the levels of citric acid in starfruit (Averrhoa Bilimbi L.) and starfruit raisins in Oti Village, Sindue Tobata District, Donggala Regency. The analytical method used to determine the levels of citric acid is alkalimetric titration. The sample used in this study came from Oti Village, Sindue Tobata District, Donggala Regency. The percentage results showed that the levels of starfruit citric acid were 6.363 %, and the starfruit raisins were 4.703 %.